Dynamic balance in former elite male athletes and in community control subjects - Raty, H. P.; Impivaara, O.; Karppi, S. L. (Scandinavian Journal of Medicine & Science in Sports, 2002)
Dynamic balance was studied in 105 former elite athletes (aged 45-68) and in 966 community control subjects (aged 27-67). Subjects walked barefoot along a 5-m-long test track, stepping only on two pads which they alternately put down in front of them and picked up from behind while standing on one foot. A better test result (short completion time) was associated with lower body mass index (in both groups), with jumping height and physical activity during the previous year (in former athletes), and with younger age, better general health, and better perceived physical fitness (in control subjects). Test results in former athletes were, on average, comparable to those of 24-30 years younger community control subjects.